Field-based assessment of the effectiveness of rust resistance genes under field conditions in Morocco and Lebanon - Nazari, Kumarse; El Amil, Rola; Al-Jaboobi, Muamar; Maafa, Ilyass; Kemal, Seid Ahmed; Ramdani, Abdelhamid; Ibriz, Hafid; SBAI, Ibtihel; Ramdhane, Nasraoui; Abdsattar, Bouslimi (International Center for Agricultural Research in the Dry Areas, 2023)
The development of rust-resistant varieties is dependent on the presence of efficient rust resistance genes, and the utilization of these genes in breeding programs relies on the evaluation of their effectiveness. Analyzing the races can offer insights into the pathogenic variations among rust pathogens and the responses of characterized genes in seedlings. Field assessments conducted under natural infection conditions provide valuable information regarding the efficacy of seedling resistance genes. Alongside the assessment of seedling resistance genes, the evaluation of sources containing adult-plant resistance genes can be carried out during the adult-plant stage. The three wheat rust trap nurseries comprising the yellow, stem, and leaf rust resistance genes were planted in several locations in Morocco and Lebanon under natural conditions. The yellow and leaf rust trap nurseries were planted at Tel Amara in Lebanon and Allal Tazi in Morocco, respectively.